A preliminary study of care coordination services within a specialized outpatient setting for youth with autism spectrum disorder. (September 2019) - Singh, Vini; Pinkett-Davis, Melanie; Kalb, Luther G.; Azad, Gazi; Neely, Jason; Landa, Rebecca
Introduction: Parents of children with autism spectrum disorder often experience high levels of stress and challenges when organizing medical and behavioral services for their child. Care coordination could alleviate these challenges, however little is known about the effectiveness of this service. This study examined the need, feasibility, and acceptability of a care coordination program. Methods: Families of 176 children with autism, seen at a multidisciplinary autism clinic in the United States, participated in a prospective observational study. Families received a three-month structured care coordination program and completed pre- and post-program questionnaires that probed parents' beliefs about the need and acceptability of the program through structured and open-ended questions. Results: Most (≥90%) parents reported both a need for care coordination and satisfaction with the program. Qualitative themes identified valuable aspects and ways to improve the program. Discussion: Parents raising a child with autism spectrum disorder experience an unmet need for care coordination. When provided, parents' demonstrated high uptake of service and high levels of satisfaction with the program.